2016
DOI: 10.1039/c6ra21663c
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable waste mitigation: biotemplated nanostructured ZnO for photocatalytic water treatment via extraction of biofuels from hydrothermal carbonization of banana stalk

Abstract: Working at the food-energy-water nexus, we identified an abundant agricultural waste with little intrinsic value – banana stalk – that can be converted to biofuels and a template for water treatment materials via hydrothermal carbonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The hydrolysis and dehydration reactions during HTC promote the production of oxygenated functional groups thus making it an effective carbon material 7 . Additionally, metallic concentrations of iron and calcium get concentrated and mediate the adsorption of anionic contaminants 8 , 9 . An increase in carbon material’s cumulative surface area with a net negative charge can be achieved by improving coarseness and promoting crack development through surface modification methodologies 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysis and dehydration reactions during HTC promote the production of oxygenated functional groups thus making it an effective carbon material 7 . Additionally, metallic concentrations of iron and calcium get concentrated and mediate the adsorption of anionic contaminants 8 , 9 . An increase in carbon material’s cumulative surface area with a net negative charge can be achieved by improving coarseness and promoting crack development through surface modification methodologies 10 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the main advantages of hydrothermal processes is that the heterogeneous wet biomass can be processed without preliminary pre-treatment such as separating and drying [9]. For these reasons, HTC is applied to various wet residues, including: grape marc [10], off specification compost [11], olive wastes [6], food wastes [12], digestate [13], sewage sludge [14][15][16] and banana stalk [17]. Our group recently demonstrated the feasibility of this technology for large-scale development through a comprehensive economic and process analysis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among natural scaffolds, eggshell membrane [146], rice [147], and banana stalks [148] have been used as biotemplates for the synthesis of ZnO NPs. Camaratta et al [146] investigated eggshell membrane-based biomimetization for the synthesis of ZnO nanostructures using zinc acetate, zinc nitrate, and zinc chloride as precursors.…”
Section: Three-dimensional Structure Generation By Nanofabricationmentioning
confidence: 99%
“…Ramimoghadam et al [147] used uncooked rice as a soft biotemplate for the hydrothermal synthesis of hexagonal wurtzite ZnO NPs with flake-like, small flower-like, tooth-like, and star-like structures. Upneja et al [148] reported banana stalks as a source of biofuel and biotemplate for the hydrothermal synthesis of ZnO nanostructures with a ~20 m 2 /g specific surface area.…”
Section: Three-dimensional Structure Generation By Nanofabricationmentioning
confidence: 99%